MEMBACA DUNIA DIBACA DUNIA: KONTRIBUSI PERPUSTAKAAN RISET - Lolytasari Lolytasari; Lilik Istiqoriyah (Maktabatuna, 2020)
This paper discusses the vision of “Membaca Dunia Dibaca Dunia” or Reading the World Reads the World which is the quality value of SPs UIN Jakarta. The research conducted is qualitative with a descriptive approach based on the results of observations and interviews with the head of the library and researchers as informants. Studies show that the more read the world is, the more advanced the institutions are. The Research Library of SPs UIN Jakarta makes an important contribution in realizing these values.